Performance Analysis of Slinky Horizontal Ground Heat Exchangers for a Ground Source Heat Pump System - Md. Hasan Ali; Keishi Kariya; Akio Miyara (Resources, 2017)
This paper highlights the thermal performance of reclined (parallel to ground surface) and standing (perpendicular to ground surface) slinky horizontal ground heat exchangers (HGHEs) with different water mass flow rates in the heating mode of continuous and intermittent operations. A copper tube with an outer surface protected with low-density polyethylene was selected as the tube material of the ground heat exchanger. Effects on ground temperature around the reclined slinky HGHE due to heat extraction and the effect of variation of ground temperatures on reclined HGHE performance are discussed. A higher heat exchange rate was experienced in standing HGHE than in reclined HGHE. The standing HGHE was affected by deeper ground temperature and also a greater amount of backfilled sand in standing HGHE (4.20 m3) than reclined HGHE (1.58 m3), which has higher thermal conductivity than site soil. For mass flow rate of 1 L/min with inlet water temperature 7 °C, the 4-day average heat extraction rates increased 45.3% and 127.3%, respectively, when the initial average ground temperatures at 1.5 m depth around reclined HGHE increased from 10.4 °C to 11.7 °C and 10.4 °C to 13.7 °C. In the case of intermittent operation, which boosted the thermal performance, a short time interval of intermittent operation is better than a long time interval of intermittent operation. Furthermore, from the viewpoint of power consumption by the circulating pump, the intermittent operation is more efficient than continuous operation.